PODER LOCAL: CONCEITO E EXEMPLOS DE ESTUDOS NO BRASIL - Márcia da Silva (Sociedade & Natureza)
The study of the diverse forms of being able (and its theories), amongst them of the State they arerelated, in this text, to the boarding and the expressed singularities in the local power. This is understoodnot as a located and locatable territorial clipping, but as a space with proper history and memory,identities and practical determined politics, that is, socially constructed. What if it can consider, inview of the carried through inquiry is that, as in the too much instances partner-territorial also in thelocal power (and perhaps until much more in it), it is uneven a plurality of being able that if they debateor if they associate (depends on the objective and the moment), as of the State, the elites, them micronpowers,the symbolic power, the power of influence etc. In this direction, shows performance to it of thesame ones in decisions real, imposed or offered for some actors and taken care of or not for others and,then, the alliances and the conflicts.